Penentuan Sistem Kerja Lift Berdasarkan Kecepatan Angkut dengan Menggunakan Simulasi ProModel (Studi Pada Sarana Lift di Universitas Bunda Mulia) - Leli Deswindi (Universitas Bunda Mulia, 2017)
The purpose of this study is to find the ideal system run for passengers elevators facilities, in term of passengers arrivals, load capacity, in and out passengers distribution to each floor, and layout of classrooms in Bunda Mulia University’s building. Four (4) models of simulations were developed in this research. The four models are: the standard (full floor services of elevators), Model 1 (odd and even services of the elevators), Model 2 (partial and full services of elevators), and model 3 (partial services of elevators). This study found two conditions. Condition 1, based on normal season with the average arrivals distribution passengers of 300 peoples / hour, the best system run of elevator passengers service is the standard model with an average waiting time of 3.88 minutes. The second conditions- with the level of infinite arrivals (unlimited) - provides Model 1 (odd and even services) as the best result), with an average waiting time of 19.26 minutes.Keywords: Simulation, Promodel, Passengers Elevator Mode